RASIO KEUANGAN SEBAGAI ALAT UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN SUMBAWA (Indonesian Journal of Social Sciences and Humanities, 2020)
This study aims to assess and evaluate the financial performance of the Sumbawa Regency regional government in 2015-2019 by using financial statement analysis in the form of financial ratios. This type of research used in this research is descriptive quantitative. The type of data used is quantitative data in the form of realization data and the regional income and expenditure budget of Sumbawa Regency in 2015-2019. Sources of data obtained through secondary data. While the data analysis technique used is financial ratios. The results explained that the regional independence ratio of Sumbawa Regency was in an instructive relationship pattern of 17.02%, the average degree of fiscal decentralization ratio was 10.47% or classified as low criteria, the regional effectiveness ratio reached 101.54% or classified as very effective. . whereas the efficiency ratio of 102.05% is classified as inefficient. Meanwhile, the regional financial capacity of Sumbawa Regency for five years in terms of share ratio and growth ratio is classified as low, namely 10.34% and 12.67% of the regional financial capacity of Sumbawa Regency in quadrant IV. Meanwhile, the regional financial performance of Sumbawa Regency in terms of income variance has increased or is at favorable criteria, while the expenditure variance has decreased negatively or is at unfavorable criteria. Therefore, the local government of Sumbawa Regency needs to optimize its resources, especially trying to better explore local potential with the aim of improving better regional financial management and capacity.